Boosting Electrochemical Activity of Porous Transparent Conductive Oxides Electrodes Prepared by Sequential Infiltration Synthesis (Small 12/2022). Issue 12 (24th March 2022) - Ko, Minkyung; Kim, Hyeong‐U; Jeon, Nari
Abstract : Electrochemistry Electrodes In article number 2105898, Nari Jeon and co‐workers present the fabrication of porous, conductive, transparent indium zinc oxides thin films using sequential infiltration synthesis. Their potential as electrodes for electrochemical applications is owed to their excellent chemical inertness, large electrochemically active surface areas, and facile surface modification with ferrocene derivatives.